Nanoparticle-based multiplex biosensor utilising dual dielectrophoretic forces for clinical diagnosis of Alzheimer's disease - Kim, Hye Jin; Ahn, Heeju; Kim, Hongrae; Park, Dongsung; Lee, Jin San; 이병철; Kim, Jinsik; Yoon, Dae Sung; Hwang, Kyo Seon (Elsevier BV, 2022)
The significant correlation between amyloid-beta (Aβ) and tau accumulated in the brain and the levels observed in plasma means that the quantification of plasma Aβ and tau is gaining attention as an alternative to conventional Alzheimer's disease (AD) diagnostic methods, such as neuroimaging and psychological memory evaluation. However, there remain limitations, such as low accuracy and reproducibility of AD diagnosis using plasma Aβ and tau quantification in clinical samples. Here, we propose an interdigitated microelectrode (IMEs)-based impedimetric biosensor that uses polystyrene beads (PS) and dielectrophoretic (DEP) force and demonstrate its clinical applicability in AD diagnosis. In the quantification of Aβ and tau present in 1% standard plasma as well as in phosphate-buffered saline (PBS), the biosensor showed almost more than 2-fold higher sensitivity compared to the reference without PS and DEP force. Furthermore, by quantifying the levels of Aβ and tau in the clinical plasma samples, we successfully distinguished between clinically diagnosed AD patients and normal controls with high accuracy (p < 0.0001). These results suggest that our biosensor has high applicability and excellent potential for the clinical diagnosis of AD.